Cyanide-Degrading Indigenous Aspergillus Spp. Isolated From Kabuto, A Southeast Sulawesi Fermented Food - Jendri Mamangkey; Nur Arfa Yanti; La Ode Adi Parman Rudia; La Ode Muhamad Iman Sulaiman; Christina Aryanti Pada Soa; Christyani Dian Winarty Budadana; Adrian Hartanto (International Journal of Health and Pharmaceutical (IJHP), 2025)
Kabuto is a traditional cassava-roots-based food of Munanese which is resulted from natural fermentation. The natural fermentation is conducted by covering all surfaces of cassava roots with fungal colonies. This experiment aims to study the cassava root fermentation by Aspergillus spp. in order to enhance the nutritive value, especially its impact on cyanide level. Both pure samples and replicated samples of cassava roots were fermented by Aspergillus spp. in a solid-state fermentation medium for six days and with a dryness level of ± 28°C. The products were analyzed to know the water content (%), the total amount of protein (mg), and cyanide detoxification (µg.g-1). Isolate K03, K23, K1c, and K31 were positively impeding activities of antimicrobials and hydrolytic enzymes (amylase and cellulase). The isolates, K03, K23, K1c, and K31 positively impeded the growth of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218. Based on the phenotypic characteristics, the isolate K03, K23, dan K1c, had similarity with Aspergillus niger, while isolate K31 had a similar microscopic and macroscopical features of Aspergillus terreus. The water content of Kabuto decreased starting on the fourth day. The isolate K03, K23, K31, and K1C preserved the water content in kabuto at 7.1%, 6.74%, 8.69%, and 7.07% respectively. The highest protein content was observed from the fermentation by Aspergillus terreus K31 (346 mg) and was able to reduce the cyanide concentration until 0.48 µg.g-1. The optimum fermentation in the preparation of kabuto was achieved at sixth day.